Epidemiological analysis of facial fractures - Tanthry, Deepalakshmi; Nehla, Aisha; Santhraya, Mahesh; Pannen, Devan Poothatta (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Facial trauma occurs in significant proportion of trauma patients requiring prompt diagnosis of fractures and soft tissue injuries with possible emergency intervention. The epidemiology of facial fractures varies with regards to Injury type, severity, and cause depending upon the population studied. The aim of the study was to understand the cause, severity and temporal distribution of facial trauma and aims in focusing on clinical and research priorities for effective treatment and prevention. It was done in the department of otorhinolaryngology at a tertiary health care centre. 100 patients between the age group of 20-60 years of both the sexes were included in the study. Patients were evaluated thoroughly with prime focus on the radiological intervention I.e., Computed tomography and X-ray. Open or closed reduction was carried out depending on the type and site of fracture. Facial fractures were found more commonly in third decade of life. Most of them had a period of hospital stay of an average of 9 days. Open reduction and internal fixation was done in cases of zygoma fractures and closed reduction was done in nasal fractures. Road traffic accidents were reported as commonest cause for facial fractures followed by assault and fall respectively. Males were the common victims. Nasal bones were the foremost fractures followed by zygomatic fractures. Closed reduction was done in nasal bone fractures. Open reduction and internal fixation was done in all cases of zygoma fractures.